Nowe tłumaczenie i interpretacja Iz 55,3-5. Studium egzegetyczno-historyczne - Zawadzki, Arnold Jan (The Biblical Annals, 2017)
The article proposes a new translation and interpretation of the messianic prophecy in Isa. 55:1-7, whose vv. 3-5 are thoroughly analyzed. The analysis includes not only the meaning of the individual words, but also the syntactic situation of the whole sentences. It was taken into account the problem of the historical context in which Deutero-Isaiah lived, worked and preached his message. This survey is designed to obtain a better understanding of the periscope, a more consistent translation and structure of the whole passage. The study undertakes an inquiry into the question of whether the eternal covenant in Isa. 55:1-7 is the continuation of the Sinaitic Covenant, or rather does its content go beyond the Mosaic Law, creating a totally new relationship of God with Israel. The study also draws attention to the existence of a redactional addition, which shifts the weight of the original message from a revanchist Judeocentrism toward the irenic ethnocentrism typical of the Book of Jonah